In Conversation with Cildo Meireles. Issue 3 (3rd July 2022) - Roman, Ana; Tymkiw, Michael
Abstract: In this interview, Brazilian artist Cildo Meireles looks back on his roughly half-century career and reflects on some recurring issues that have defined his art. Key among them: a spectator's act of walking or stepping on the ground; the iterative nature of Meireles's process for making installations; and his interest in space, place, and circulation. The interview originally took place in October 2019, shortly after the opening of the artist's retrospective Entrevendo—Cildo Meireles at SESC Pompéia; it has since been supplemented with material from exchanges with Meireles between August 2020 and May 2021.